2019
DOI: 10.18034/ajtp.v6i3.352
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Corporate Social Responsibility Disclosure of Islamic Shari-based Banking Companies in Bangladesh

Abstract: The purpose of this study is to examine the current extent and any difference (if any) of CSR disclosure of Islamic Sharia-based banking companies in Bangladesh during the period of 2011-2015.  Content analysis is adopted to accumulate the data from company’s annual reports. The CSR checklist comprise of sixteen dimensions (including 85 items) of CSR activities i.e., ‘Environment’, Disaster management, ‘Sports, Shelter, Women, Disabled, Liberation war, Health, Education, Energy, Minorities, Employee, Product r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Besides, Bangladesh has developed and adopted several rules and regulations. These laws also monitor communal and environmental issues for companies operating in Bangladesh (Hossain & Neogy, 2019). In reality, a weak governance, lack of proper policies and guidelines, as well Journal of Sustainability Science and Management Volume 15 Number 8, December 2020: 136-166 as an absence of resilient political stimulus along with deficiency of skilled workforces and expertise hindered the implementation of these laws (Belal et al, 2015).…”
Section: Csr Disclosures and Institutional Background Of Bangladeshmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, Bangladesh has developed and adopted several rules and regulations. These laws also monitor communal and environmental issues for companies operating in Bangladesh (Hossain & Neogy, 2019). In reality, a weak governance, lack of proper policies and guidelines, as well Journal of Sustainability Science and Management Volume 15 Number 8, December 2020: 136-166 as an absence of resilient political stimulus along with deficiency of skilled workforces and expertise hindered the implementation of these laws (Belal et al, 2015).…”
Section: Csr Disclosures and Institutional Background Of Bangladeshmentioning
confidence: 99%
“…Explicitly, through the procedure of regulatory guidelines of the Bangladesh Bank (BB), inspiration and other initiatives have helped to generate participation in sustainability activities through a more systematic approach since 2008 (Hossain et al, 2019). For instance, intending to start green finance, BB delivered a guideline to confirm that the financial sector has methods to reduce environmental pollution when funding new ventures (BB, 2008;Masud & Kabir, 2016).…”
Section: Csr Disclosures and Institutional Background Of Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, CSR disclosure practices of the Islamic banking industry depends on some specific dimensions of CSR (Hossain and Neogy, 2019). Another study on the CSR disclosure practices in the banking sector identified that CSR disclosure practices depends on factors like government ownership, age, Islamic compliance and CSR expenditures (Saha, 2019).…”
Section: Bangladesh Perspectivementioning
confidence: 99%
“…opposed to the CSR actions associated with core business that are pursued by conventional banks. Hossain & Neogy[33] empirically experimented the statistically significant difference of CSR disclosure among Islamic Sharia-based banking companies in Bangladesh which reveals is no significant difference of CSR disclosure of Islamic banking industry in Bangladesh during the period of 2011-2015 by considering 16 dimensions including Environment, Disaster management, Sports, Shelter, Women, Disabled, Liberation war, Health, Education, Energy, Minorities, Employee, Product responsibility, IT, Community and Government. Overall, so many researches have been conducted only to know the financial performance of banks but few have been researched on understanding the role of CSR in the sustainable development of a country.…”
mentioning
confidence: 99%